Freedom of literary thought of the Andalusian personality in the fifth century AH (Texas Journal of Philology, Culture and History, 2023)
We note that the freedom of the Andalusian personality witnessed a rapid and strong start and wide practices were manifested through the poets and writers of Andalusia and Andalusia rose in the fifth century AH a broad intellectual and literary renaissance in various cultural and literary fields and was able to achieve independence , A clear intellectual and literary view of the Orient in the affairs of culture and civilization., And that the Cultural that influenced the process of freedom of literary thought of the Andalusian person in this era has an important role in poetry , literature, intellectual development and culture in general, especially that this century witnessed a general cultural and intellectual renaissance that had its clear effects in the development of literature and the prosperity of its arts, and that the literary and intellectual independence of the Andalusian person in the fifth century Hijri was evident through the writers and poets who emerged in that century